OP79 Improving Public Understanding Of Scottish Medicines Consortium Advice. (2019) - Dickson, Jennifer; Taylor, Louise; McCormack, Jackie; Downes, Noreen; Lockhart, Lindsay; Walker, Laura
Abstract : Introduction: Transparency of processes and decision making is important to the Scottish Medicines Consortium (SMC). An independent review of access to new medicines in Scotland in 2016 recommended that SMC should review its communication of decisions with a view to achieving greater transparency. SMC therefore began to develop plain English summaries of advice on each new medicine. Methods: A multi-stakeholder approach was adopted to develop the summary documents, with patient groups involved. Firstly, a review of communications for the public from other HTA organizations was conducted. The public involvement team then held a workshop to find out what patient groups felt would be important to include when explaining SMC decisions to patients and the public. The process was also informed by reviewing examples of good practice from other parts of NHSScotland, including patient versions of Scottish Intercollegiate Guidelines Network (SIGN) clinical guidelines. Exemplar documents were then developed and feedback sought from the Public Involvement Network Advisory Group. Results: A format was developed for the SMC 'Decision Explained' summaries consisting of a question and answer format for each medicine decision in a two page document. The summaries were piloted internally over a six month period, during which the development process and layout were finalized. Since September 2018 these summaries have been published on the website alongside the technical advice. Conclusions: Partnership working between SMC and patient groups has helped to develop a new way of communicating SMC's decisions to patients and the public in a clear way, helping to improve transparency and understanding. Evaluation of the summaries will be undertaken from six months of publication.